Sprouting Angiogenesis in Human Pituitary Adenomas - Zhou, Jie; Hu, Yaomin; Zhu, Wende; Nie, Chuansheng; Zhao, Wenxiu; Faje, Alexander T.; Labelle, Kay E.; Swearingen, Brooke; Lee, Hang; Hedley-Whyte, E. Tessa; Zhang, Xun; Jones, Pamela S.; et al. (Frontiers in Oncology, 2022)
Introduction: Angiogenesis in pituitary tumors is not fully understood, and a better understanding could help inform new pharmacologic therapies, particularly for aggressive pituitary tumors. Materials and Methods: 219 human pituitary tumors and 12 normal pituitary glands were studied. Angiogenic genes were quantified by an angiogenesis qPCR array and a TaqMan probe-based absolute qPCR. Angiogenesis inhibition in pituitary tumors was evaluated in vitro with the endothelial tube formation assay and in vivo in RbΔ19 mice. Results: 71 angiogenic genes, 40 of which are known to be involved in sprouting angiogenesis, were differentially expressed in pituitary tumors. Expression of endothelial markers CD31, CD34, and ENG were significantly higher in pituitary tumors, by 5.6, 22.3, and 8.2-fold, respectively, compared to in normal pituitary tissue. There was no significant difference in levels of the lymphatic endothelial marker LYVE1 in pituitary tumors compared with normal pituitary gland tissue. Pituitary tumors also expressed significantly higher levels of angiogenesis growth factors, including VEGFA (4.2-fold), VEGFB (2.2), VEGFC (19.3), PGF (13.4), ANGPT2 (9.2), PDGFA (2.7), PDGFB (10.5) and TGFB1 (3.8) compared to normal pituitary tissue. Expression of VEGFC and PGF were highly correlated with the expression of endothelial markers in tumor samples, including CD31, CD34, and ENG (endoglin, a co-receptor for TGFβ). Furthermore, VEGFR inhibitors inhibited angiogenesis induced by human pituitary tumors and prolonged survival of RbΔ19 mice. Conclusion: Human pituitary tumors are characterized by more active angiogenesis than normal pituitary gland tissue in a manner consistent with sprouting angiogenesis. Angiogenesis in pituitary tumors is regulated mainly by PGF and VEGFC, not VEGFA and VEGFB. Angiogenesis inhibitors, such as the VEGFR2 inhibitor cabozantinib, may merit further investigation as therapies for aggressive human pituitary tumors.